Identifying Beliefs and Cognitions Underpinning Commuters' Travel Mode Choices - Mann, E.; Abraham, Samuel (Wiley-Blackwell Publishing Inc., 2012)
Interventions to reduce car use have shown limited success, in part due to limitations in models of transport choices. The theory of planned behavior (TPB) has provided a useful predictive model of car use but the specific beliefs that underpin TPB-specified cognitions are less well understood. In this study, 229 university employees responded to a questionnaire and then reported their commuting choices 1 week later. Intention and perceived behavioral control (PBC) predicted car use (R2=.79). Intention was predicted by attitude, subjective norm, PBC, and moral norm (R2=.56). Beliefs could not be differentiated into attitudinal and PBC constructs, but seven beliefs predicted TPB cognitions. A similar model was tested for public transport use. The results identify key targets for future interventions.